Bioactive terpenoids from Silybum marianum and their suppression on NO release in LPS-induced BV-2 cells and interaction with iNOS. Issue 10 (15th May 2017) - Qin, Ning-Bo; Li, Sheng-Ge; Yang, Xue-Yuan; Gong, Chi; Zhang, Xiang-Yu; Wang, Jian; Li, Da-Hong; Guo, Yuan-Qiang; Li, Zhan-Lin; Hua, Hui-Ming
Graphical abstract: Abstract: Three new (1 –3 ) and one known (4 ) bioactive terpenoids were isolated from the seeds of Silybum marianum based on the investigation to get new NO inhibitors. Their structures were determined by extensive NMR (1D and 2D NMR) and MS spectroscopic data, and the absolute configurations were identified by experimental and calculated ECD spectra. The NO inhibitory activities in murine microglial BV-2 cells and interactions with iNOS protein by molecular docking were evaluated for all compounds. The results showed that these compounds had potent NO inhibitory effects.